Effects of spine flexion and erector spinae maximal force on vertical squat jump height: a computational simulation study - Blache, Y.; Momteil, K. (Sports Biomechanics, 2015)
The purpose of this study was to evaluate the single and combined effects of initial spine flexion and maximal isometric force of the erector spinae on maximal vertical jump height during maximal squat jumping. Seven initial flexions of the `thorax-head-arm` segment (between 20.1° and 71.6°) and five maximal isometric forces of the erector spinae (between 5600 and 8600 N) were tested. Thus, 35 squat jumps were simulated using a 2D simulation model of the musculoskeletal system. Vertical jump height varied at most about 0.094 and 0.021 m when the initial flexion of the `thorax-head-arm` segment and the maximal force of the erector spinae were, respectively, maximal. These results were explained for the most part by the variation of total muscle work. The latter was mainly influenced by the work produced by the erector spinae which increased at most about 57 and 110 J when the initial flexion of the `thorax-head-arm` segment and the maximal force of the erector spinae were, respectively, maximal. It was concluded that the increase in the initial flexion of the `thorax-head-arm` segment and in the maximal isometric force of the erector spinae enables an increase in maximal vertical jump height during maximal squat jumping.